Cutaneous Adnexal Cysts Revisited: What We Know and What We Think We Know - Gürkan Kaya; Jean-Hilaire Saurat (MDPI AG, 2018)
Cutaneous cysts have been classified by dermatopathologists in many different ways. Here, we propose a novel classification of cutaneous adnexal cysts according to their origin in the folliculosebaceous unit and the sweat glands. By examining the lining of the cystic structure, its origin can be easily identified. Epidermal cysts have an epithelial wall containing a granular layer with lamellar keratinization, indicating an infundibular origin. Tricholemmal cysts have an undulating epithelial wall with no granular layer and a compact keratinization, showing an isthmic origin. In steatocystoma, dermoid cyst, and folliculosebaceous hamartoma, the epithelial lining shows a crenulated appearance which is seen in the sebaceous duct. Hidrocystoma shows the characteristic cuboidal epithelial lining of sweat glands with decapitation secretion in its apocrine forms. The hair matrix cyst wall is composed of basaloid cells maturing to squamoid cells, as seen in the normal hair matrix and shadow cells in the lumen. Metabolizing acquired dioxin-induced skin hamartoma (MADISH) is a cystic lesion with lamellar keratinization, and no sebaceous glands. The classification proposed here aims to simplify the complexity of cutaneous adnexal cysts, and to facilitate a better understanding of the origin of cystic lesions of the skin.